Thoracic trauma update. Issue 3 (March 2023) - Pumphrey, Oliver; Burnside, Nathan
Abstract: The management of chest trauma has adapted and advanced with developing technologies and research. The biggest fundamental change has come with the update in the ATLS guidelines which rewrite some of the basic steps in the initial approach to these acutely unwell patients. Evolving techniques used in elective thoracic surgical practice have advanced trauma care with increased utilization of chest wall fixation equipment, a move towards video-assisted thoracic surgery, and the innovation in extra-corporeal oxygenation techniques. This update reviews the integration of these approaches into trauma care.